Tiller-specific formulated fertilizer improves the population tiller quantity and yield of machine-transplanted rice - Jun Deng; Xuehuan Liao; Jun Shi; Qi Xu; Xinyu Yang; Ran Wang; Jianming Ding; Lubing Jia; Xiaotian Jiang; Shengmin Yan; Rongping Zhang; Yungao Hu; et al. (PLoS ONE, 2026)
Abstract Delayed harvest of the previous crops of the rice-based rotation systems in Sichuan often leads to late transplanting of rice, thus extending the seedling age and shortening the effective growth period after the recovery of machine-transplanted seedlings. To improve the seedling survival rate and root growth after mechanical transplantation, as well as to promote tillering and regreening, a two-factor split-plot experiment was conducted. The main plot factor was the application of tiller fertilizer, and the subplot factor was the rice variety. Two fertilizer treatments were established, namely compound fertilizer (CK) and formula-specific tiller fertilizer (T1), where CK was used as the control. Four hybrid rice varieties were Longliangyou 534 (V1), Yunliangyou 332 (V2), Taifengyou 208 (V3), and Nei 6 You 6368 (V4). This study investigated the effects of the formulaic tiller fertilizer on the tillering rate, growth, development, and yield of machine-transplanted hybrid rice. The results showed that the effective panicle rate of rice increased by 1.26% under the T1 treatment compared to that under CK. Ten days after tillering, the length and fresh weight of tiller buds were 53.65% and 67.06% notably higher in T1 than those in CK. Additionally, the bud length was peaked in V4. Compared with CK, T1 treatment significantly increased the content of auxin (IAA), endogenous zeatin + zeatin riboside (Z + ZR), and the ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC) in tiller buds, while reducing the content of abscisic acid (ABA). Additionally, the formula-based tiller fertilizer remarkably enhanced the activity of Ca² ⁺ -Mg² ⁺ -ATPase. Compared to CK, the yield contributions of the main stem, primary tillers, and secondary tillers under treatment T1 increased by 6.96%, 18.42%, and 8.86% in 2022, respectively. Among all treatments, the V3T1 treatment resulted in the highest yields of the main stem and primary tillers, with yield contribution rates of 9.79% and 56.63%, respectively. In 2023, the yields of the main stem, primary tillers, and secondary tillers under T1 were higher than those under CK. Specifically, T1 had the highest yield contribution rate from primary tillers, whereas the contribution rate of secondary tillers was lower than that of CK. For the V4 growth stage, T1 also produced the highest yields of the main stem, primary tillers, and secondary tillers, at 988.49 kg/hm², 5,432.55 kg/hm², and 5,050.10 kg/hm², respectively. Therefore, formula-specific tiller fertilizer(T1) exhibited a significant yield-increasing effect on hybrid rice, with greater yield potential observed in V3 and V4. These findings provide a technical reference for mechanized transplantation cultivation of rice in the hilly rice-growing areas of northwestern Sichuan.